Investigations on the effectiveness of sewage purification in medium sand with assisting middlings coal layer - Marek Kalenik (Acta Scientiarum Polonorum. Formatio Circumiectus)
Aim of the study: The objective of these investigations is to check in laboratory conditions whether a middlings coal assisting layer with the granulation 0.02 - 5 mm, introduced into the ground, improves the efficiency of nitrogen and phosphorus compounds removal from domestic sewage.